PEMENUHAN HAK ANAK MELALUI PROGRAM DIVERSI PADA ANAK YANG BERKONFLIK DENGAN HUKUM MELALUI RESTORATIVE JUSTICE - Kaboel Suwardi (Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 2017)
Justice for children in conflict with lawshould be interpreted essentially as a, whichare permanent and will continue to give toeveryone what should have for him: Iustitiaconstans et est voluntas ius suum Perpetuacuiqe tribuendi. Changing the philosophy ofjuvenile delinquency treatment of perpetratorsof the retributive or rehabilitative model ofrestorative justice, which basically takes theconcept of John Braithwaite’s theory ofReintegrative Shaming.This model could be in line with theapproach underlying the rules and values inthe Convention on Rights of the Child is anapproach to welfare, in which young offendersas much as possible be kept away from theprocess of condemnation of the criminal justicesystem.This model can be obtained through aresponsive legal thought through approach tohandling model of restorative justice withchildren in conflict with law through diversionprogram, which is a way to settle the caseoutside the formal system of law enforcement(non litigation).Key words: child rights, restorative justice,diversion